VALUE FOR MONEY AND YOUTH RIDERSHIP IN URBAN PUBLIC TRANSPORT: EVIDENCE FROM KUALA LUMPUR - Ismail, Zuraidah; Sulaiman, Saliza; Asmuni, Shahariah; Samsudin, Fauziah; Ramlan, Natasha (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2026)
This study examines public transport usage behaviour among young adults in Kuala Lumpur, with particular emphasis on travel frequency, mode choice, perceived affordability, service quality, and future usage intention. Drawing on the Theory of Planned Behaviour, Public Choice Theory, and the Value-for-Money framework, the study analyses survey data collected from 108 respondents aged 18 to 25 years. Descriptive and inferential analyses are employed to evaluate patterns of use and identify key determinants of ridership behaviour. The findings indicate that while public transport is widely perceived as affordable and cost-saving largely due to government subsidy schemes such as student discounts and monthly passes usage remains irregular for many young adults. Rail-based services, particularly the LRT and MRT, emerge as the most preferred modes owing to their speed and network coverage, alongside increasing evidence of multimodal travel. Correlation results reveal that affordability, subsidies, safety, service sufficiency, and cleanliness significantly influence intention to continue using public transport, with safety and service sufficiency exerting the strongest effects. The study is significant in highlighting the need to have an overall strategy in place to retain young commuters to promote sustained youth mobility through public transport in developing cities. The findings also provide implications for public transport planning and public transport strategies in developing cities in general.